On the guiding principles for understanding of geometrical structures of the CaMn4O5 cluster in oxygen-evolving complex of photosystem II. Proposal of estimation formula of structural deformations via the Jahn–Teller effects. (4th March 2017) - Yamaguchi, K.; Shoji, M.; Isobe, H.; Yamanaka, S.; Umena, Y.; Kawakami, K.; Kamiya, N.
ABSTRACT: Atmospheric oxygenation and evolution of aerobic life on our earth are a result of water oxidation by oxygenic photosynthesis in photosystem II (PSII) of plants, algae and cyanobacteria. The water oxidation in the oxygen-evolving complex (OEC) in PSII is expected to proceed through five oxidation states, known as the S i ( i = 0, 1, 2, 3 and 4) states in the Kok cycle, with the S1 being the most stable state in the dark. The OEC in PSII involves the active catalytic site made of four Mn ions and one Ca ion, namely the CaMn4 O5 cluster. Past decades, molecular structures of the CaMn4 O5 cluster in OEC in PSII have been investigated by the extended X-ray absorption fine structure (EXAFS). The magneto-structural correlations were extensively investigated by electron paramagnetic resonance (EPR) spectroscopy. Recently, Kamiya and Shen groups made great breakthrough for determination of the S1 structure of OEC of PSII by the X-ray diffraction (XRD) and X-ray free-electron laser (XFEL) experiments, providing structural foundations that are crucial for theoretical investigations of the CaMn4 O5 cluster. Large-scale quantum mechanics/molecular mechanics calculations starting from the XRD structures elucidated geometrical, electronic and spin structures of the CaMn4 O5 cluster, indicating an important role of the Jahn–Teller (JT) effect of Mn(III) ions. This paper presents theoretical formulas for estimation of the JT deformations of the CaMn4 O5 cluster in OEC of PSII. Scope and applicability of the formulas are examined in relation to several different structures of the CaMn4 O5 cluster proposed by XRD, XFEL, EXAFS and other experiments. Implications of the computational results are discussed for further refinements of geometrical parameters of the CaMn4 O5 cluster. GRAPHICAL ABSTRACT: